2015
DOI: 10.1186/s13561-015-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast and cervical cancer screening in Great Britain: Dynamic interrelated processes

Abstract: No previous analysis has investigated the determinants of screening uptake for breast and cervical cancer screening for possible spillover effects from one type of screening examination to the other type of screening examination with a dynamic bivariate panel probit model. For our analysis, we used a dynamic random effects bivariate panel probit model with initial conditions (Wooldridge-type estimator) and dependent variables were the participation of breast and cervical cancer screening in the recent year. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…In particular, it has been demonstrated that the decision to participate in one form of cancer screening or periodic health assessment can positively influence the decision to participate in other forms of cancer screening, including breast and cervical ( 38 , 39 ) and the completion of colorectal, prostate (PSA) and mammography screening ( 40 ). A decision made potentially easier if screening services were available to the person on the same day and at the same location.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been demonstrated that the decision to participate in one form of cancer screening or periodic health assessment can positively influence the decision to participate in other forms of cancer screening, including breast and cervical ( 38 , 39 ) and the completion of colorectal, prostate (PSA) and mammography screening ( 40 ). A decision made potentially easier if screening services were available to the person on the same day and at the same location.…”
Section: Discussionmentioning
confidence: 99%
“…the spillover effect of a cholesterol level check on blood pressure check and vice versa. A spillover effect has also been found for the breast and cervical cancer screening examination in Great Britain 6 . This spillover effect could be explained by the fact that an individual is more accessible for preventive information if one of the cardiovascular screening examination has been done in the past or the individual is advised also to do the other type of cardiovascular screening examination.…”
Section: Discussionmentioning
confidence: 80%
“… 59 and Devicienti et al . 50 ) and this model has been used to analyse the simultaneous uptake of the breast and cervical cancer screening examination 6 and also in further panel data applications 60 – 62 . The Wooldridge estimator specifies a relationship between the unobserved time-invariant individual effect and the observed characteristics and has the assumption of initial conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low prevalence of kidney cancer, such a ‘bolt on’ screening programme may well be the most cost-effective as well as the most acceptable. It may also increase uptake of existing programmes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%